2021
DOI: 10.1016/j.jclinepi.2021.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of prognostic clinical prediction models based on machine learning methods in oncology needs to be improved

Abstract: Objective: Evaluate the completeness of reporting of prognostic prediction models developed using machine learning methods in the field of oncology.Study design and setting: We conducted a systematic review, searching the MEDLINE and Embase databases between 01/01/2019 and 05/09/2019, for non-imaging studies developing a prognostic clinical prediction model using machine learning methods (as defined by primary study authors) in oncology. We used the Transparent Reporting of a multivariable prediction model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…An overall median TRIPOD score of 0.48 (range: 0.17-0.79) signifies that, on average, more than half of the critical information for study development was not reported. Strikingly, our findings are to a large extent in keeping with a recently published systematic review investigating TRIPOD adherence in clinical prediction models in oncology using ML [69]: Dhiman et al also found low adherence for Title, Abstract. and Predictor blinding; reporting on Background/Objectives and overall interpretation of study results was similarly high in our study cohort; major differences could be seen in the reporting of missing data, where our reviewed articles showed significantly lower adherence; however, given that Dhiman et al investigated clinical prediction models, it is likely that their results do not translate immediately to ML models based on imaging.…”
Section: Discussionsupporting
confidence: 92%
“…An overall median TRIPOD score of 0.48 (range: 0.17-0.79) signifies that, on average, more than half of the critical information for study development was not reported. Strikingly, our findings are to a large extent in keeping with a recently published systematic review investigating TRIPOD adherence in clinical prediction models in oncology using ML [69]: Dhiman et al also found low adherence for Title, Abstract. and Predictor blinding; reporting on Background/Objectives and overall interpretation of study results was similarly high in our study cohort; major differences could be seen in the reporting of missing data, where our reviewed articles showed significantly lower adherence; however, given that Dhiman et al investigated clinical prediction models, it is likely that their results do not translate immediately to ML models based on imaging.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings suggest that the algorithms appeared to have promising overall discriminatory performance with respect to AUROC values, consistent with previous studies summarizing the performance of ML-based models supporting mortality predictions for other populations [ 16 - 19 ]. However, the results must be interpreted with caution because of the high ROB across the studies, as well as some evidence of the selective reporting of important performance metrics such as sensitivity and PPV, supporting previous studies reporting poor adherence to TRIPOD reporting items in ML studies [ 52 ]. We identified several common issues that could lead to biased models and misleading model performance estimates in the methods used to develop and evaluate the algorithms.…”
Section: Discussionsupporting
confidence: 75%
“…There is also no assurance on how AI models will be monitored and audited in the event of adverse outcomes. Recent publications from the fields of sports medicine and oncology reflect these complexities ( 21 , 22 ).…”
Section: The Chaos Of Humans and Healthcarementioning
confidence: 99%